Pancreatogastrostomy Versus Pancreatojejunostomy for RECOnstruction After PANCreatoduodenectomy (RECOPANC, DRKS 00000767): Perioperative and Long-term Results of a Multicenter Randomized Controlled Trial. Issue 3 (March 2016) - Keck, Tobias; Wellner, U. F.; Bahra, M.; Klein, F.; Sick, O.; Niedergethmann, M.; Wilhelm, T. J.; Farkas, S. A.; Börner, T.; Bruns, C.; Kleespies, A.; Kleeff, J.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: To assess pancreatic fistula rate and secondary endpoints after pancreatogastrostomy (PG) versus pancreatojejunostomy (PJ) for reconstruction in pancreatoduodenectomy in the setting of a multicenter randomized controlled trial. Background: PJ and PG are established methods for reconstruction in pancreatoduodenectomy. Recent prospective trials suggest superiority of the PG regarding perioperative complications. Methods: A multicenter prospective randomized controlled trial comparing PG with PJ was conducted involving 14 German high-volume academic centers for pancreatic surgery. The primary endpoint was clinically relevant postoperative pancreatic fistula. Secondary endpoints comprised perioperative outcome and pancreatic function and quality of life measured at 6 and 12 months of follow-up. Results: From May 2011 to December 2012, 440 patients were randomized, and 320 were included in the intention-to-treat analysis. There was no significant difference in the rate of grade B/C fistula after PG versus PJ (20% vs 22%, P = 0.617). The overall incidence of grade B/C fistula was 21%, and the in-hospital mortality was 6%. Multivariate analysis of the primary endpoint disclosed soft pancreatic texture (odds ratio: 2.1, P = 0.016) as the only independent risk factor. Compared with PJ, PG was associated with an increased rate of grade A/B bleeding events, perioperative stroke, less enzyme supplementation at 6 months, and improved results in some quality of life parameters. Conclusions: The rate of grade B/C fistula after PG versus PJ was not different. There were more postoperative bleeding events with PG. Perioperative morbidity and mortality of pancreatoduodenectomy seem to be underestimated, even in the high-volume center setting.